Analisis Perbandingan Kinerja Keuangan Bank Syariah dan Bank Konvensional di Bursa Efek Indonesia Tahun 2019–2024 berdasarkan Rasio Keuangan - Maysharah Sugiarsih; Khairiyani Khairiyani (Lembaga Yasin AlSys, 2025)
This study is motivated by the inconsistencies found in previous research regarding the comparison of financial performance between Islamic and conventional banks in Indonesia. The fundamental differences in operational systems and financial management principles between the two types of banks have the potential to generate variations in profitability, efficiency, and capital resilience. The objective of this research is to analyze and compare the financial performance of Islamic and conventional banks listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period, based on five key financial ratios: Return on Assets (ROA), Loan to Deposit Ratio / Financing to Deposit Ratio (LDR/FDR), Non-Performing Loan / Non-Performing Financing (NPL/NPF), Capital Adequacy Ratio (CAR), and the Operating Expenses to Operating Income ratio (BOPO). A quantitative approach was used with purposive sampling, involving eight banks as the sample—four Islamic banks and four conventional banks. Data were obtained from annual financial reports and analyzed using the Independent Sample T-Test and Mann-Whitney test. The results reveal significant differences in the NPL/NPF and CAR ratios between Islamic and conventional banks, while no significant differences were found in ROA, LDR/FDR, and BOPO. These findings indicate that Islamic banks demonstrate superior performance in financing quality and capital adequacy, whereas conventional banks outperform in operational efficiency and fund intermediation functions.